Pengaruh Lingkungan Kerja dan Konflik Kerja terhadap Turnover Intention Karyawan pada PT Tayoh Sarana Sukses - Tungga Buana Irfana; Asna Oktavi Dismarani; Tungga Buana Diana (Universitas 45 Surabaya, 2024)
This study aims to determine how much influence the work environment and work conflict have on employee turnover intention at PT. Tayoh Sarana Sukses. The population in this study were employees of PT.Tayoh Sarana Sukses. Sampling method using Sampling in this study using purposive sampling technique (sample considerations), namely the sampling unit selected based on certain considerations with the aim of obtaining a sampling unit that has characteristics. With the slovin formula technique. The sample used in this study were 92 employees. This study uses quantitative methods with multiple linear regression analysis, hypothesis testing using t test and f test with a significance level of 5%. Based on the t-test the work environment has a significant effect on turnover intention and work conflict has a significant effect on turnover intention. And based on the f test, the work environment and work conflict together have a significant effect on turnover intention.